2021
DOI: 10.1002/ldr.3975
|View full text |Cite
|
Sign up to set email alerts
|

Shrub‐encroached grassland as an alternative stable state in semiarid steppe regions: Evidence from community stability and assembly

Abstract: Understanding community restoration state and assembly mechanisms is helpful to assess restoration measures and predict community dynamics. In order to explore the effects of fencing duration and shrub cover on community stability and assembly, we investigated the community information and assessed the assembly mechanisms in plots using shrub cover of Caragana microphylla within each of the three sites fenced since 1979, 1983, and 2003 in a semiarid steppe region of China. Community composition was different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…In this study, the finding that most of the absolute values of SESs were lower than 1.96 indicated that random processes dominated the community assembly in the study site or perhaps that there was a balance between environmental filtering and limiting similarity. In the Inner Mongolia steppe, random processes usually dominate community assembly in the early stage of restoration succession or in harsh local environmental conditions with low soil nutrient status (Hao et al, 2021; Koyama et al, 2015). However, there was significant difference between the responses of SESs assessed by both approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the finding that most of the absolute values of SESs were lower than 1.96 indicated that random processes dominated the community assembly in the study site or perhaps that there was a balance between environmental filtering and limiting similarity. In the Inner Mongolia steppe, random processes usually dominate community assembly in the early stage of restoration succession or in harsh local environmental conditions with low soil nutrient status (Hao et al, 2021; Koyama et al, 2015). However, there was significant difference between the responses of SESs assessed by both approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The different letters show significant differences (p < 0.05) among different shrub canopy removal treatments under a fixed distance from shrubs. The "*" in the bracket show significant (p < 0.05) differences between two sampling distance treatments under a fixed removal frequency [Colour figure can be viewed at wileyonlinelibrary.com] assembly in the early stage of restoration succession or in harsh local environmental conditions with low soil nutrient status (Hao et al, 2021;Koyama et al, 2015). However, there was significant difference between the responses of SESs assessed by both approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Beta diversity can be partitioned into two different components: turnover component (some species disappear and replaced by others) and nestedness component (the assemblages of sites with smaller numbers of species are subsets of the assemblages at richer sites), which can provide insight into the processes that maintain biodiversity (Baselga, 2010;Legendre, 2014). Shrub encroachment is an irreversible process with potential effects on the soil environmental heterogeneity and plant communities, thus affecting the beta diversity of soil communities (Hao et al , 2021). On the one hand, shrubs, which function as habitat for soil communities, could limit the range of potential colonizers by favoring or excluding species with particular functional attributes, which would directly decrease beta diversity of soil communities (Siegwart Collier & Mallik, 2010;Wardhaugh et al , 2012;Lanta et al , 2018;Xiang et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, shrub triggers large shifts in plant communities and soil environmental heterogeneity, indirectly affecting beta diversity of soil communities. For example, plant communities could affect niche space and niche differentiation for soil communities; environmental heterogeneity may increase the variation in abiotic factors that limit local species coexistence (Chesson, 2000;Schöb et al , 2013;Trentanoviet al , 2013;Losapio et al , 2018;Albrecht et al , 2021;Hao et al , 2021). These processes would alter the turnover and nestedness components between habitats, resulting in changes in beta diversity of soil communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation